Web Design and Marketing Solutions for Business Websites - Potts, Kevin (Apress : Imprint: Apress, 2007)
The best business websites serve their readers with strong content, well-architected design, and a focus on usability, readability, and accessibility. This book covers the fundamental aspects of building a website that works for the company, not against it. It covers the essentials of strong copywriting, and then dedicates several chapters to designing user-centric About, Products and Services, and Support sections. Your visitors come to your site because they are interested in your business and are therefore potential customers. This book covers taking advantage of that traffic by expanding the company's story through a corporate blog and using testimonials, case studies, and other third-party validation to reinforce the marketing message. With this knowledge, you will be able to create and maintain a highly professional, polished business site. While a pleasing website is essential for any modern business, creating it is only a small piece of the online strategy. This book also discusses search engine optimization, using e-mail and RSS to communicate with customers and prospects, and advertising the corporate domain with paid search placement, online banners, text links, and more. The primary theme is using your corporate website to market the business effectively, from designing intelligent product pages to writing compelling e-mail newsletters. This book explores those ideas and offers compelling advice on how to take full advantage of the Web as a marketing medium.